Selecting a robust decision making method to evaluate employee performance. (14th June 2019) - Haddad, M.; Sanders, D.; Bausch, N.
This paper investigates how to select a robust decision making method to evaluate employee performance. Two multiple criteria decision making (MCDM) methods are considered for the evaluation of US coast guard officers. Sensitivity analysis is conducted to understand the nature of uncertainty in evaluation criteria and employee performance. Outcomes from this analysis provide an understanding of the most critical factors governing the evaluation. MCDM methods dealing with discrete sets of alternatives are considered. The stability of two MCDM methods' outcomes are compared and the method with the most stable outcome is recommended. The minimum percentage change in criteria weights and performance scores required to alter the outcome of the evaluation is calculated. An MCDM method is recommended based on a best compromise in minimum percentage change required in inputs to alter the outcome of a method.